2011 Atlanta Conference on Science and Innovation Policy 2011
DOI: 10.1109/acsip.2011.6064474
|View full text |Cite
|
Sign up to set email alerts
|

Co-evolution of policies and firm level technological capabilities in the Indian automobile industry

Abstract: Innovation in form of new products, processes or forms of productive organisation brings growth to firms and development to economies and therefore it is important to understand sources of innovation and technological capabilities. In this context this paper explores sources of innovation and technological capability in the Indian automobile industry. In last decade Indian auto industry emerged as one of the fastest growing industry with increasing levels of technological sophistication in auto industries amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Hierarchical preferences posit that (a) some goods might not be purchased because of affordability and (b) additional income is used to consume high priority goods (Foellmi & Zweimüller, 2008). With these assumptions, one can infer that high-income consumers induce high-quality and differentiated products with high acquisition costs, whereas low-income consumers stimulate products with relatively low price and low acquisition costs (Kale, 2011;Kaplinsky, 2011). Thus, this pattern creates heterogeneity in the income elasticity of demand (Fajgelbaum, Grossman, & Helpman, 2011).…”
Section: The Impact Of Income Inequality On Entrepreneurshipmentioning
confidence: 99%
“…Hierarchical preferences posit that (a) some goods might not be purchased because of affordability and (b) additional income is used to consume high priority goods (Foellmi & Zweimüller, 2008). With these assumptions, one can infer that high-income consumers induce high-quality and differentiated products with high acquisition costs, whereas low-income consumers stimulate products with relatively low price and low acquisition costs (Kale, 2011;Kaplinsky, 2011). Thus, this pattern creates heterogeneity in the income elasticity of demand (Fajgelbaum, Grossman, & Helpman, 2011).…”
Section: The Impact Of Income Inequality On Entrepreneurshipmentioning
confidence: 99%
“…As a result, firms operating in emerging markets are offering various options to customers, making the markets highly aggressive with features such as competitive pricing and access to availability of finance with long‐term return options. In the case of the automobile industry, Kale (2011) reported that the Indian market is skewed towards mini, compact and fuel‐efficient vehicles instead of luxury cars: as per Sagar and Chandra (2004), the segment preferring mini and compact cars contributes to 80 per cent of total car sales in India.…”
Section: An Illustrative Case Of Maruti Suzuki In Indiamentioning
confidence: 99%
“…Suzuki responded to the requirement for affordable passenger vehicles in India by offering low‐cost cars to Indian customers. Considering the stage that the economy of India was at in 1983 and the operational requirements of the Indian market, Suzuki decided to join hands with the local authorities through a public‐private partnership under the name of Maruti Suzuki (Kale, 2011). Following its entry into the Indian market, Suzuki associated with local firms to understand the key attributes of the market at the micro level.…”
Section: An Illustrative Case Of Maruti Suzuki In Indiamentioning
confidence: 99%
See 2 more Smart Citations